Healing the exposed being : a South African Ngoma tradition - Thornton, Robert J. (Wits University Press, 2018)
This ethnography explores the Ngoma healing tradition as practiced in eastern Mpumalanga, South Africa. u2018Bungomau2019 is an active philosophical system and healing practice consisting of multiple strands, based on the notion that humans are intrinsically exposed to each other and that this is the cause of illness, but also the condition for the possibility of healing. This healing seeks to protect the u2018exposed beingu2019 from harm through augmenting the self. Unlike Western medicine, it does not seek to cure physical ailments but aims to prevent suffering by allowing patients to transform their personal narratives of Self. Like Western medicine, it is empirical and is presented as a u2018local knowledgeu2019 that amounts to a practical anthropology of human conflict and the environment. The book seeks to bring this anthropology and its therapeutic applications into relation with global academic anthropology by explaining it through political, economic, interpretive, and environmental lenses.